Факторы конкурентоспособности предпринимательских структур (Путеводитель предпринимателя)
The article examines the main reasons that determined the increased attention to the competitiveness of business structure. Proposes a definition of competitiveness on the basis of summarizing the definitions formulated by representatives of domestic and foreign economic thought. The author considers the problem of competitiveness at the micro, meso and macro levels, as well as the factors (external and internal to the enterprise structure), the competitiveness of business structure.